THE FORMATION OF THE INSTITUTE OF INDEPENDENT RATING AGENCIES - V. Ukolov; A. Solomatin; A. Nikienko (Вестник университета)
The article considers problems of formation of the Institute of independent rating agencies and substantiated ways of their solution. Are different points of view regarding the objectivity of the ratings given by international rating agencies and the author argues about the feasibility of creating such structures on the space of States outside the European Economic Union.